Pengaruh Brand Ambassador, Brand Trust terhadap Keputusan Pembelian : Studi Kasus Brand Uniqlo pada Konsumen Treasure Maker - Shafira Putri Ramsaranti; Djoko Hananto (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This research is motivated by the use of Korean idols as brand representatives by well-known brands such as UNIQLO has become an interesting marketing phenomenon to study, especially in the context of fandom in Indonesia. The purpose of this study is to examine how Brand Ambassador and Brand Trust influence the purchasing decisions of Treasure Maker consumers in South Tangerang City to purchase UNIQLO products. This research is an associative quantitative research with a purposive sampling approach using a questionnaire as a data collection tool. This study used 96 Treasure Maker respondents who had purchased UNIQLO X Treasure in South Tangerang City as samples. This study uses multiple linear regression analysis processed using SPSS 25, with the results showing that partially Brand Ambassador has a positive and significant effect on Purchasing Decisions, Brand Trust has a positive and significant effect on Purchasing Decisions, while Brand Ambassador and Brand Trust also have a positive and significant effect on purchasing decisions simultaneously. These findings indicate that the presence of the right brand ambassador and a high level of brand trust can help customers make better purchasing decisions.